Crisis Management From An Islamic Perspective: An Assessment Of The Islamic Affairs And Charitable Activities Department In Dubai - Ahmed Shuhail Alqahtani, Abdalla Abdelrahman (2020)
Human global expansion with its increased consumption has placed an unprecedented strain on resources, leading to political and economic turmoil necessitating proper management. This caused the emergence of a new form of thinking that analyses crises and attempts to provide acceptable solutions with the least negative outcomes. In today’s society, crises are phenomenon that every organization has to be prepared for. Persons engaged in crisis management (CM) need to develop strategies to manage crises. CM is a strategic planning process that requires the institution to take a set of decisions in circumstances of tension and uncertainty, at a specific time aimed at the proper response to the events of the crisis and preventing its escalation and minimizing its negative results to the least possible extent and removing risks in the direction of restore their natural conditions.